Genetic short stature. (February 2018) - Grunauer, Michelle; Jorge, Alexander A.L.
Abstract: Adult height and growth patterns are largely genetically programmed. Studies in twins have indicated that the heritability of height is high (> 80%), suggesting that genetic variation is the main determinant of stature. Height exhibits a normal (Gaussian) distribution according to sex, age, and ancestry. Short stature is usually defined as a height which is 2 standard deviations (S.D.) less than the mean height of a specific population. This definition includes 2.3% of the population and usually includes healthy individuals. In this group of short stature non-syndromic conditions, the genetic influence occurs polygenically or oligogenically. As a rule, each common genetic variant accounts for a small effect (1 mm) on individual height variation. Recently, several studies demonstrated that some rare variants can cause greater effect on height, without causing a syndromic condition. In more extreme cases, height SDS below 2.5 or 3 (which would comprise approximately 0.6 and 0.1% of the population, respectively) is frequently associated with syndromic conditions and are usually caused by a monogenic defect. More than 1, 000 inherited/genetic diseases have growth disorder as an important phenotype. These conditions are usually responsible for syndromic short stature. In the coming years, we expect to discover several genetic causes of short stature, thereby explaining the phenotype of what we currently classify as short stature of unknown cause. These discoveries will have a profound impact on the follow-up and treatment of these children. Highlights: In this review we discuss the main genetic aspects that influence height and determination of short stature. We review recent literature to give an overview of the subject. This text reflects the lecture presented during THE 2 nd USFQ BIENNIAL ON GH & IGF1 RESEARCH – 2017 in Quito, Ecuador.